Gender disparities in multiple sclerosis research and leadership: A Colombian perspective - Casallas-Vanegas, Adriana; Guío-Sánchez, Claudia; Reyes-Mantilla, María I.; Restrepo-Aristizábal, Carolina; Navas-Granados, Angela; Guerrero-Gómez, Alejandra; Zuluaga, María I. (Frontiers in Neurology, 2022)
Background: The neurological academic field is an illustrative example of persistent gender-related disparities reflected in compensation, funding, leadership, promotion, publishing, and recognition. Several studies indicate that neurology is one of the most underrepresented specialties with female physicians as first author, but also has one of the highest gender payment gaps. Neglecting the role of women in academic leadership positions hinders the visibility and recognition of research and leadership in Multiple Sclerosis (MS). Objective: The aim of our study is to establish the gender distribution between researchers and clinical neurologists in multiple sclerosis in Colombia and raise awareness about gender disparities in this area. Methods: We applied a cross-sectional survey study of Colombian neurologists and neurology residents currently members of the Colombian Neurology Association. Mean and standard deviation (SD) were used for quantitative variables and frequency for qualitative variables. To evaluate the influence of gender, logarithmic regression was used. Data was analyzed in SPSS 26. Results: A total of 201 participants agreed to complete the survey, most of whom were female (n=135, 67.2%). Of those surveyed, 31.5% (n=64) had an interest in demyelinating diseases and MS, of which 46.8% (n=30) were female. Of the women with MS training, only 50% (n=5) had more than three publications as first author of a scientific article compared to men (n=5, 83%). There were no significant differences between men and women (median 2.0[2, 1.21] ​​vs 2[2, 0.5], p=0.904). However, only 16.6% (n=5) of women had a visible academic, leadership, or teaching position compared with men 75.7% (n=25). When adjusting the salary income by gender, we found a statistically significant difference among women and men (median 2.0 [5, 1.47] ​​vs 3 [5, 1.65], p=0.006). Women in MS earned between USD 2,500 and 3,800 per month; while men earned between USD 3,800 to 5,070. Conclusion: Despite a higher number of female neurologists trained in MS in Colombia, our data suggest considerable differences and gender gaps with regard to diverse opportunities at the academic, salary promotion, leadership, teaching, and recognition levels between male and female MS neurologists.